Functional Tea-Infused Set Yoghurt Development by Evaluation of Sensory Quality and Textural Properties - Katarzyna Świąder; Anna Florowska; Zuzanna Konisiewicz; Yen-Po Chen (Foods, 2020)
In the present study, the potential to design natural tea-infused set yoghurt was investigated. Three types of tea (Camellia sinensis): black, green and oolong tea as well as lemon balm (Melissa officinalis L.) were used to produce set yoghurt. The sensory quality (using Quantitative Descriptive Profile analysis and consumer hedonic test) and texture analysis, yield stress, physical stability and colour analysis were assessed to describe the profile of the yoghurt and influence of quality attributes of the product on the consumer acceptability of infused yoghurts in comparison with plain yoghurt. Among the analyzed plant additives for yoghurt, addition of 2% oolong tea to the yoghurt allows a functional food to be obtained with satisfactory texture and sensory properties, accepted by consumers at the same level as for control yoghurt. Both types of yoghurt were also characterised by high consumer willingness to buy, which confirms the legitimacy of using oolong tea as a natural, functional yoghurt additive that improves the sensory quality of the product. The high overall quality of yoghurt with oolong tea in comparison to other plant extracts was associated with the intensive peach flavour and odour, nectar and sweet odour and flavour, and the highest creaminess and thickness. That was confirmed by principal component analysis (PCA) where the overall sensory quality of yoghurts was mainly positively correlated with peach flavour and odour, sweet odour and yoghurt odour, while it was negatively correlated with herbs flavor and odour, and green tea flavour and odour. The sensory profile confirmed no differences in textural profile between plain yoghurt and the tea-infused one measured in the mouth, which corresponds to the result of textural properties such as firmness and adhesiveness.